The world of department stores - Whitaker, Jan (Vendome Press, 2011)
"This is the first beautifully illustrated book on department stores, with photographs and ephemera from all over the world. Born in the Gilded Age in France, the department store grew up thanks to the industrial revolution, the rise of the middle class, and the invention of steel-frame architecture and the elevator. Spectacular entrances led to marble staircases and floor after floor of merchandise and amenities. These emporiums also inspired a whole new way of merchandising: shopping became an entertainment rather than a laborious grind; posters and advertisements were made by the great artists of the time; and elaborate shop windows attracted thousands of people during the holidays. The department store quickly spread through Europe and Asia and then the New World, and great architects were employed to build these temples of consumerism, where dreams were created and then fulfilled"-- Provided by publisher.